Sistem Pendukung Keputusan Menentukan Lokasi Rumah Burung Walet (RBW) Menggunakan Metode AHP dan SAW - Pradipta, Anjar; Amin, Muh.; Sumpala, Andi Tenri; Sutoyo, Muh. Nurtanzis (Jurnal Sains dan Informatika, 2019)
Swallow's nests are sold as ingredients for soups and raw materials for medicines. Because the price of swiftlet nests is very expensive so many people have started to build a swallow bird house (RBW) by spending a considerable amount of money for swallow bird cultivation. But to build RBW and grow swallow birds requires an exact and optimal location. This study aims to create a system for determining the location of a computerized swallow house construction by implementing the Analytic Hierarchy Process (AHP) method and the Simple Additive Weighting (SAW) method in determining the exact location of swallow bird house construction to reduce the level of loss and error in site selection. The AHP method is used in estimating the value of each parameter that is determined while the SAW method is used in assessing levels. Based on the 6 criteria for swallow bird locations, namely location height, distance from the city center (industry), air temperature, distance from rice fields / plantations, distance from waterways, and distance from other buildings, the decision support system built can be a choice of solutions to facilitate farmers and swallow nest entrepreneurs in determining the exact and optimal location of swallow bird houses.